2020
DOI: 10.3390/ijms21186964
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides as New Combination Agents in Cancer Therapeutics: A Promising Protocol against HT-29 Tumoral Spheroids

Abstract: Antimicrobial peptides are molecules synthetized by a large variety of organisms as an innate defense against pathogens. These natural compounds have been identified as promising alternatives to widely used molecules to treat infections and cancer cells. Antimicrobial peptides could be viewed as future chemotherapeutic alternatives, having the advantage of low propensity to drug resistance. In this study, we evaluated the efficiency of the antimicrobial peptide gramicidin A (GA) and the anticancer drug, doxoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 62 publications
1
14
0
1
Order By: Relevance
“…Similar to our results, there were numerous tryptophan rich AMPs applied efficiently against cancer cells grown in monolayer [34][35][36][37]. However, we reported previously the effect of Gramicidn A against HT-29 spheroids showing that the peptide alone is efficient, destabilizing the spheroids, while in combination with a tumoral drug the effect is amplified [29].…”
Section: Pic Self-assemblies Increased Antitumor Potential Of P6 Against Hct-116 Spheroidssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our results, there were numerous tryptophan rich AMPs applied efficiently against cancer cells grown in monolayer [34][35][36][37]. However, we reported previously the effect of Gramicidn A against HT-29 spheroids showing that the peptide alone is efficient, destabilizing the spheroids, while in combination with a tumoral drug the effect is amplified [29].…”
Section: Pic Self-assemblies Increased Antitumor Potential Of P6 Against Hct-116 Spheroidssupporting
confidence: 90%
“…Cell viability was assessed using the MTT assay as described previously [29]. After desired treatment times (24 and 48 h) the culture medium was removed from each well, MTT was added at a final concentration of 1 mg/mL and the spheroids were further incubated at 37°C for 4h.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…assessed the efficiency of Gramicidin A and doxorubicin against the spheroids from colorectal cancer cells. The assessment of cancer cell viability confirmed that both doxorubicin (EC50: 15.31 μg/ml) and Gramicidin A (EC50: 9.78 μM) induce cytotoxic effects against the cancer cell spheroids separately, whereas their combination reduces the cancer cell viability synergistically ( 5 ). In another study, 150 μg/ml of KT2 and RT2 inhibited the HCT-116 cell proliferation by 70.65% and 69.01%, respectively.…”
Section: The Antineoplastic Roles Of Amps In Various Cancer Typesmentioning
confidence: 84%
“…Along with topical administration, the safety of intravenous injection of some AMPs was evaluated. In this regard, the safety and tolerability of human lactoferrin [1][2][3][4][5][6][7][8][9][10][11] were assessed in the life-threatening infections of patients with hematological malignancies who received hematopoietic stem cell transplantation (HSCT). The results showed that patients could tolerate up to 5-mg single dose of hLF1-11 intravenously (174).…”
Section: Clinical Applications Of Amps In Anticancer Therapymentioning
confidence: 99%
See 1 more Smart Citation